Penalty of model misspecification in time series dominated with trend - Chukwudi Justin, Ogbonna; Chijioke Joel, Nweke; Kelechi Charity, Ojide (International Journal of Advanced Mathematical Sciences, 2019)
Model specification is consequential in mathematical science and statistics in particular. This work seeks to ascertain the consequences of model mis-specification in the analysis of a time series dominated by trend. It further discusses the statistical properties of various types of trend as well as when they are combine with AR (1) and MA (1) process. It recommends the use of spectrum analysis in detection of trend type in a given series.Illustrations were carried out using simulated series. The results from the simulated series was in harmony with the theoretical results.Â Â